Squalus acanthias, spiny dogfish - Finucci, B. (2020)
While there are reported subpopulations of Squalus acanthias (Linnaeus, 1758) elsewhere in the world, the North Pacific subpopulation is now considered a separate species, Squalus suckleyi (Girard, 1854) (see Ebert et al. 2010). Further taxonomic studies on this genus are required, including in relation to Mediterranean and Black Sea subpopulations. In Europe, three subpopulations are inferred to occur.